Cropping System Intensification: An Approach to Increase Yield, Water Productivity, and Profitability in North-West Bangladesh - Md. Belal Hossain; Md. Towfiqul Islam; Debjit Roy; Mir Nurul Hasan Mahmud; Priya Lal Chandra Paul; Mst. Shetara Yesmin; Palash Kumar Kundu; Nazmun Nahar Karim; Md. Abdul Kader; Md. Humayoun Kabir (International Journal of Agronomy)
Water productivity improvement is getting the prime concern to sustain irrigated rice production in the water-scarce areas of Bangladesh under changing climate. Besides, profitable cropping pattern selection is one of the major indicators of commercial agriculture. The study was conducted at Mithapukur and Pirganj Upazilas of Rangpur district during 2018–2020 to evaluate the water saving and profitability of three crop cropping patterns over two crops pattern. The experiment involved two improved patterns, T. Aman-Mustard-Boro (CP1) and T. Aman-Potato-Boro (CP2), and one locally popular pattern, T. Aman-Fallow-Boro (CP3). Irrigation management involved supplemental irrigation for T. Aman rice, irrigation application after disappearing standing water for Boro rice, and two irrigations at critical stages of potato and mustard. Both CP1 and CP2 received higher rainfall than CP3 because the delayed transplanting of Boro rice captured more rainfall. The improved patterns of CP1 and CP2 saved 22–40% of irrigation water compared with CP3. Among the patterns, CP2 achieved the highest rice equivalent yield (REY) of 21.1–33.6 t·ha−1 due to excellent potato production. Similarly, CP2 provided the highest irrigation water productivity because of higher REY as well as less irrigation requirement. Both CP1 and CP2 patterns returned a higher gross margin than CP3. The findings indicated that the inclusion of potato and mustard in the T. Aman-Fallow-Boro cropping pattern saved irrigation water as well as increased production and economic benefit. Adoption of these water-efficient cropping patterns may reduce groundwater irrigation in the water-scarce areas of Bangladesh.